1999
DOI: 10.1074/jbc.274.9.5925
|View full text |Cite
|
Sign up to set email alerts
|

Possible Involvement of Proteasomes (Prosomes) in AUUUA-mediated mRNA Decay

Abstract: We have identified a cellular target for proteasomal endonuclease activity. Thus, 20 S proteasomes interact with the 3-untranslated region of certain cytoplasmic mRNAs in vivo, and 20 S proteasomes isolated from Friend leukemia virus-infected mouse spleen cells were found to be associated with a mRNA fragment showing great homology to the 3-untranslated region of tumor necrosis factor-␤ mRNA that contains AUUUA sequences. We furthermore demonstrate that 20 S proteasomes destabilize oligoribonucleotides corresp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 37 publications
1
37
0
Order By: Relevance
“…It has previously been shown that the 20S core proteasomal complex was able to digest single-stranded RNA. [2][3][4][5] However, it was unclear whether the fully assembled 26S complex retained the ability to degrade RNA. To address this question, we decided to examine whether the biochemically purified intact 26S proteasome complex exhibited RNase activity in vitro ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has previously been shown that the 20S core proteasomal complex was able to digest single-stranded RNA. [2][3][4][5] However, it was unclear whether the fully assembled 26S complex retained the ability to degrade RNA. To address this question, we decided to examine whether the biochemically purified intact 26S proteasome complex exhibited RNase activity in vitro ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It should be noted, that the same authors demonstrated the inability of 20S core proteasomes to degrade cellular messenger RNA. [2][3][4][5] Thus, it remains unclear whether the 26S proteasome is a large multi-subunit protein complex involved in proteolytic degradation of proteins. In addition to its canonical proteolytic activity, the proteasome is also associated with recently characterized endoribonuclease (endoRNAse) activity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[51][52][53] Moreover, a number of transcripts encoding proteasome-associated and F-box proteins were identified in Arabidopsis developing and germinating pollen. 42,54 Proteasomes were also demonstrated to perform other nonproteolytic functions including transcriptional regulation, [55][56][57] RNase activity, 58,59 translational regulation, 60,61 and possessing cytoskeleton-binding properties. 52,62 With regard to all abovementioned alternative functions, the presence of proteasome subunits within EPP complexes is natural in relation to complex EPP-associated spatially and temporarily regulated activities.…”
Section: Discussionmentioning
confidence: 99%
“…Three copies of the consensus sequence, ATTTA, are present at positions 1661-1665, 1677-1681, and 1790-1794. This motif, which also is found in human PPET-1 cDNA [10], is proposed to mediate selective translationdependent destabilization of mRNA, as was demonstrated for cytokine genes [5,8,13]. Structural analysis of the deduced prepropolypeptide demonstrates that regions corresponding to a bioactive mature ET-1 peptide (C 53 -W 73 ), an intermediate form big ET-1 (C 53 -S 91 ), and an endothelinlike (ET-like) peptide (C 110 -Q 125 ) are found on the deduced polypeptide, as they are in other mammals including humans [9], mice [16], rats [24], and pigs [33].…”
Section: Full-length Cdna Sequence and Primary Protein Structure Of Pmentioning
confidence: 99%